Identification and functional characterization of Epstein-Barr virus DNA polymerase by in vitro transcription-translation of a cloned gene. - Lin, J C (1991)
In order to identify the gene encoding the Epstein-Barr virus (EBV) DNA polymerase, a portion of the BamHI-A fragment containing the fifth leftward open reading frame (BALF5) of the EBV genome was cloned into SP6 and T7 promoter-containing vectors for in vitro transcription-translation. The RNA synthesized in vitro was used to program rabbit reticulocyte lysates, which were analyzed for the synthesis of the putative polymerase polypeptide (110 kDa) and assayed directly for EBV DNA polymerase activity. The polypeptide synthesized by the full-length BALF5 genomic fragment had a molecular mass of 110 kDa. 5'-truncated BALF5 with the first and second ATGs deleted produced 95- and 83-kDa polypeptides, respectively. All three translation products were enzymatically active and displayed resistance to high salt concentrations. The identity of the largest polypeptide as the viral polymerase was established by (i) immunoprecipitation with EBV-positive sera from patients with nasopharyngeal carcinoma and by a rabbit polyclonal antiserum prepared with a synthetic peptide derived from the DNA sequence of BALF5; (ii) identification of a polypeptide of identical size (110 kDa) immunoprecipitated from superinfected Raji cell extracts by these antibodies; and (iii) salt-resistant enzymatic activity which was neutralized by the rabbit EBV antiserum. Thus, BALF5 encodes a functional polymerase identical to that induced in superinfected Raji cells.